1986
DOI: 10.1161/01.res.58.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of myocardial blood flow associated with experimental canine left ventricular hypertrophy secondary to valvular aortic stenosis.

Abstract: SUMMARY. Experimental renovascular hypertension or supravalvular aortic constriction results in left ventricular hypertrophy and impaired minimum coronary vascular resistance. However, these experimental models expose the coronary arteries to increased intra-arterial pressure, so that hypertensive vascular changes might be responsible for the impaired minimum coronary resistance. This study was performed to test the hypothesis that left ventricular hypertrophy in the absence of increased coronary pressure resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 31 publications
6
31
1
Order By: Relevance
“…28 The effect of intraventricular pressure changes on MBF is also poorly understood, with conflicting evidence from animal models. 29,30 In our study there was a clear relationship between a reduction in hemodynamic workload, as demonstrated by the change in AVA, and increase in CVR, which, in the absence of epicardial stenosis, suggests an improvement in coronary microcirculatory function in these patients after AVR. 31 Shortened DPT in AS results in blunting of myocardial perfusion, 2,32 particularly during tachycardia.…”
Section: Changes In Coronary Perfusion and Microcirculatory Function supporting
confidence: 60%
“…28 The effect of intraventricular pressure changes on MBF is also poorly understood, with conflicting evidence from animal models. 29,30 In our study there was a clear relationship between a reduction in hemodynamic workload, as demonstrated by the change in AVA, and increase in CVR, which, in the absence of epicardial stenosis, suggests an improvement in coronary microcirculatory function in these patients after AVR. 31 Shortened DPT in AS results in blunting of myocardial perfusion, 2,32 particularly during tachycardia.…”
Section: Changes In Coronary Perfusion and Microcirculatory Function supporting
confidence: 60%
“…53 The same abnormality was described during exercise 54,55 in a pressure overload model produced by aortic banding in puppies. This was attributed to a reduced subendocardial coronary reserve related in part to the larger compressive forces in the subendocardium where stress is larger.…”
Section: Myocardial Perfusionmentioning
confidence: 63%
“…Furthermore, at the higher level of coronary perfusion pressure the absolute value of coronary flow rate under control perfusion or maximal vasodilation did not decrease compared with sham-operated controls (Fig. 5, A (4,6,9) indicate that the physiological coronary vascular abnormalities do not always coexist with cardiac muscle hypertrophy. Therefore, it is possible that the abnormalities in coronary circulation persist even after complete regression of cardiac muscle hypertrophy produced by pressure overload with coronary arterial hypertension.…”
Section: Regression Ofmyocardial Hypertrophy and Coronary Vascular Chmentioning
confidence: 86%
“…In hypertrophied hearts, abnormalities in coronary circulation such as decreased coronary blood flow per unit muscle mass (2), increased coronary vascular resistance during maximal vasodilation (3)(4)(5)(6)(7)(8)(9), impaired autoregulation (10), changes in transmural blood flow distribution (3, 9-13), or decreased coronary flow reserve (6)(7)(8)(9)(14)(15)(16)(17)(18)(19)(20)(21)(22) have been reported in clinical and animal studies. If the hemodynamic load is normalized, cardiac muscle hypertrophy regresses in patients and animals (1,(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation